The results of a pilot study on immersive Virtual Reality to boost learner-to-learner mediation strategies in Italian as a foreign language - Compagnoni, Ilaria (Glottodidactica, 2024)
The development of immersive technologies in language education has led to pedagogical experimentations on enhancing students’ collaborative skills through task-based immersive Virtual Reality (iVR), a technology that allows users to experience real-like interactions with objects and other individuals. Despite positive correlations between the use of iVR in language learning and task accomplishment (Chen et al. 2022; Wu & Hung 2022; Romano et al. 2023), evidence is missing on the development of mediation strategies in a foreign language (FL), regarding learner-tolearner mediation strategies. Therefore, this study presents the results of a pilot study conducted at the University of Siena (Italy) on a pair of students of Italian as FL. The students were involved in digital multimodal composing (DMC) activities on the iVR platform Immerse. Results showed that mediation strategies surfaced through verbal and non-verbal facilitations of peer interactions, meaning-making, conceptual talk encouragement, and interaction management. It also highlighted methodological considerations on using iVR to involve language students in training scenarios for the development of mediation skills transferrable to real-life socio-pragmatic contexts.